Altered T cell plasticity favours Th17 cells in early arthritis - Leipe, Jan; Pirronello, Fausto; Schulze-Koops, Hendrik; Skapenko, Alla (Rheumatology, 2020)
The predominance of differentiated Th17 cells has been implied as a key driver of autoimmune arthritis, including early RA. Because accumulating evidence suggests that Th cell differentiation is a plastic process, we investigated plasticity and underlying molecular mechanisms to address the shift towards the Th17 phenotype in early RA.A cohort of 61 patients with early, active, untreated RA and 45 age- and sex-matched healthy controls were studied. Viable in vitro- and in vivo-generated Th1, Th2 and Th17 cells were FACS-sorted and transdifferentiated under Th1-, Th2- or Th17-inducing conditions. The cytokine Th profile of the transdifferentiated cells was assessed by flow cytometry. Th cell-associated cytokine and transcription factor gene loci were analysed by chromatin immunoprecipitation assay and their expression by quantitative real-time PCR.In vitro-generated Th cells showed substantial plasticity, which was similar between RA and healthy controls, whereas in vivo-derived Th1 and Th2 cells from RA patients demonstrated an enhanced plasticity towards IL-17-expressing phenotypes compared with healthy controls. Further, in vivo-generated Th17 cells from RA patients showed a resistance to transdifferentiate into Th1 or Th2 cells. The serum/glucocorticoid-regulated kinase 1-forkhead box protein O1-IL-23 receptor (SGK1-FOXO1-IL-23R) axis together with increased RORC expression was associated with the predominant Th17 phenotype in early RA.Our data indicate that in vivo-originated Th subsets are prone to Th17 cell transdifferentiation in early RA, while Th17 cells are resistant to changes in their phenotype. Together, the data imply that an altered plasticity contributes to the Th17 shift in early RA.
Gesehen am 26.05.2025